Impact of usage of electronic devices on sleep quality among healthcare professions students in Ajman, UAE - Abouelenen, Shahd; Kayali, Zeina; Hamra, Tariq; Bessila, Dania; Sreedharan, Jayadevan (International Journal of Public Health Science (IJPHS), 2024)
Due to the advancement in technology, people are using various electronic devices. People using electronics and the internet at inappropriate times may have a harder time falling asleep and have less sleep duration, and the sharp rise in electronic device use has numerous adverse effects. This study aimed to assess the impact of the usage of electronic devices on sleep and also to determine the factors influencing sleep among healthcare professions students. A cross-sectional study was conducted using a self-administered questionnaire. The association was assessed using the Chi-square test and simple binary logistic regression to identify the factors. Of the total 446, 36.4% reported not having problems during the past month in getting to sleep within 30 minutes. Internet use at school during a typical weekday, 22.2% use 2-4 hours a day; outside of school during a typical weekday, 24.7% use >6 hours. 34.3% use the internet >6 hours outside of school on weekends. The crude OR observed was 4.1, 3.7, 3.6 and 3.9 for 1-2, 2-4, 4-6, >6 hours respectively which is statistically significant. Factors that showed statistical significance for sleep duration were nationality and internet use outside the school during a typical weekend day. For how long it takes to fall asleep, the age group was the factor that showed statistical significance.